The Effect of Polychronicity on Employee Engagement: Conditional Process of Job Satisfaction and Compensation - Rian Andriani; Disman Disman (Journal of Economics, Business, and Accountancy Ventura, 2023)
The health industry has the third highest voluntary turnover rate in the world; thus, the degree of participation in the health industry is still relatively low. Low employee engagement continues to make employee engagement an intriguing issue of study, notably in Indonesia. According to a survey, 76%Â of employees are not engaged in their work. This study aims to investigate the effect of polychronicity on employee engagement with the conditional process of job satisfaction as a mediating variable and compensation as a moderating variable. Testing the model using the PROCESS statistical tool version 3.5, the sample was determined based on the Slovin formula so that 212 individuals participated in the study. According to the findings, compensation is effective in moderating the effect of polychronicity on job satisfaction, compensation is effective in moderating the effect of polychronicity on employee engagement, and compensation is effective in moderating the effect of job satisfaction on employee engagement. Each interaction is in a high category. The study implicates the result of the analysis of the conditional process model on the effect of polychronicity, job satisfaction, and compensation on employee engagement in the health industry.